The Analysis of Using Spatial Smoothing for DOA Estimation of Coherent Signals in Sparse Arrays - Haiyun Xu; Weijia Cui; Yuxi Du; Fengtong Mei; Bin Ba (International Journal of Antennas and Propagation)
When there is coexistence of uncorrelated and coherent signals in sparse arrays, the conventional algorithms for direction-of-arrival (DOA) estimation using difference coarray fail. In order to solve the problems, this paper analyzes the feasibility of using spatial smoothing in sparse arrays. Firstly, we summarize the two types of sparse arrays, one consisting of identical sparse subarrays and the other consisting of several uniform linear subarrays. Then, we give the feasibility analysis and the processes of applying spatial smoothing. At last, we discuss the performance of the number of detectable coherent signals in different sparse arrays. Numerical experiments prove the conclusions proposed by the paper.